ANTIBACTERIAL PROPERTY AND MOLECULAR DOCKING STUDIES OF METHANOLIC FUNGAL PHYTOCHEMICALS OF CLAVICEPS PURPUREA INFECTED TO BAJRA (PENNISETUM GLAUCUM) CROP - LOKESH ST; THIPPESWAMY B; RAVIKUMAR S (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study is to study the antibacterial activity, minimum inhibitory concentration, preliminary phytochemical studies, molecular docking studies, and high-resolution liquid chromatography mass spectrometer (HR-LCMS) analysis of the methanol fungal extract of Claviceps purpurea. Methods: Mass production of the fungal mat of C. purpurea was established on potato dextrose broth medium. The dried methanol extract of fungus was subjected to HR-LCMS analysis; antibacterial screening of the extract was carried out against pathogenic bacteria. Molecular docking study of HR-LCMS identified compounds was performed by docking with bacterial enzyme DNA gyrase. Results: HR-LCMS analysis of methanol extract of C. purpurea fungus shows that the compounds arecoline, benperidol, felbamate, solanidine, and triparanol as the major constituents. The antibacterial screening of methanol extract of fungus against bacterial pathogens showed a significant bactericidal activity against the strains Pseudomonas aeruginosa (14.40±0.04 mm), Xanthomonas campestris (13.60±0.06 mm), Escherichia coli (13.40±0.06 mm), Salmonella Typhi (11.50±0.05 mm), Staphylococcus aureus (11.37±0.04 mm.), and as matched to the standard drug ciprofloxacin. The molecular docking of triparanol against the bacterial enzyme DNA gyrase showed good binding affinity of −6.2 kcal/mol, good drug likeness (7.3767), 2 hydrogen bonds, and hydrophobic interaction with 8 amino acid residues so that triparanol shows good inhibitor as compared to other 4 compounds. Conclusion: Methanol fungal extract of C. purpurea showed significant antibacterial activity against pathogenic bacteria. Triparanol is the major compound present in C. purpurea fungus which showed good inhibitory activity against bacterial enzyme DNA gyrase. The methanol extract of C. purpurea fungus displayed a good antibacterial drug.